Evaluation of the Nurses’ Practices Concerning Vaccination at Primary Health Care Centers in Al-Amarah City - Ghazwan A. Abd Al-Wahid; Arkan B. Nagi (Kufa Journal for Nursing Sciences)
Objective: To evaluate the nurse’s practices and to find out association between practices and their demographic characteristics of age, gender, education, and training crosses.